2011
DOI: 10.1016/j.neuropharm.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-induced modulation of LTD at GABAergic synapses in the ventral tegmental area

Abstract: Plasticity of dopamine (DA) neurons of the ventral tegmental area (VTA) plays an essential role in addiction. Previously we discovered a form of long‐term potentiation at GABAergic synapses onto VTA DA neurons that is prevented with morphine. The objective of this study was to investigate whether the same GABAergic synapses are capable of exhibiting long‐term depression (LTD) and whether morphine modulates it. Using whole‐cell patch clamp recording, we found that the efficacy of VTA GABAergic synapses can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…3). Previous studies have also shown that a single in vivo injection of morphine is able to trigger long-lasting changes in synaptic strength of GABAergic synapses (Dacher and Nugent 2011;Nugent et al 2007). Here we demonstrated (pA) saline (12) morphine (13) saline+CI-994 (5) morphine+CI-994(11) * * * * * * before after that morphine per se induced a reduction in GABAergic synaptic strength by suppressing GABA release and decreasing the number or function of postsynaptic GABA A Rs (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3). Previous studies have also shown that a single in vivo injection of morphine is able to trigger long-lasting changes in synaptic strength of GABAergic synapses (Dacher and Nugent 2011;Nugent et al 2007). Here we demonstrated (pA) saline (12) morphine (13) saline+CI-994 (5) morphine+CI-994(11) * * * * * * before after that morphine per se induced a reduction in GABAergic synaptic strength by suppressing GABA release and decreasing the number or function of postsynaptic GABA A Rs (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Long-term potentiation (LTP) of glutamatergic synapses onto VTA DA neurons can be triggered 24 h after a single in vivo exposure to opioids and other drugs promoting DA cell excitability and behavioral sensitization (Brown et al 2010;Saal et al 2003;Ungless et al 2001). Moreover, a single exposure to a drug of abuse such as morphine has been shown to block LTP and may occlude long-term depression (LTD) at GABAergic synapses onto VTA DA neurons, further enhancing DA signaling from the VTA (Dacher and Nugent 2011;Nugent et al 2007).…”
Section: Learning Mechanisms In Brain Reward Pathways Are Hijacked Afmentioning
confidence: 99%
“…This effect was also not dependent on endocannabinoid signaling, but was blocked by the dopamine D2 receptor (D2R) antagonist sulpiride. Interestingly, a single morphine injection was sufficient to prevent LFS-induced LTD GABA 24 hours after administration, suggesting that morphine can bidirectionally regulate GABA plasticity in VTA (Dacher and Nugent 2011a).…”
Section: Acute Opiate-induced Synaptic Plasticitymentioning
confidence: 98%
“…More recently, another form of VTA GABAergic plasticity has been described: longterm depression of GABAergic synapses onto DA neurons (LTD GABA ) (Dacher and Nugent 2011a). Using low-frequency stimulation (LFS), a stable LTD GABA in DA cells was induced that, in contrast to LTP GABA , was expressed postsynaptically and did not depend on NMDAR.…”
Section: Acute Opiate-induced Synaptic Plasticitymentioning
confidence: 99%
“…This D 2 R activation requires a neurochemical signaling via inhibitory G protein-PKA-inositol phosphate receptor IP 3 R-Ca 2+ -calcineurin-A-kinase anchoring protein 150 AKAP150 at GABAergic synapses (Dacher et al, 2013). Importantly, LTD GABA is abolished/occluded by a single dose of morphine 24 hours before the measurements (Dacher and Nugent, 2011a). Collectively, morphine-induced changes in LTP GABA and LTD GABA represent forms of inhibitory plasticity that together with changes in excitatory synapses provide a mechanism to enhance mesolimbic DA transmission and thereby increase the incentive properties of morphine (Dacher and Nugent, 2011b).…”
Section: G Opioid-induced Neural Adaptationsmentioning
confidence: 99%